IMPROVING STUDENTS' LISTENING COMPREHENSION IN NARRATIVE TEXT BY USING DICTOGLOSS TECHNIQUE - Endriati, Win; Sutapa Yuliana, Yohanes Gatot; Bunau, Eusabinus (Journal of English Educational Study (JEES), 2024)
Abstract:The research was conducted based on the problems that were found in the teaching and learning process. The students faced some problems in listening to the narrative text: writing the right vocabulary based on the teacher's pronunciation, identifying important supporting details, and drawing inferences. The purpose of this research was to investigate how the Dictogloss technique improved students'listening comprehension in listening narrative text on the eleventh grade students in class XI IPS 3 of SMAN 5 Pontianak in the academic year 2017/2018. The results showed that the implementation of the dictogloss technique in this research is successful in improving students' listening comprehension in the narrative text, and the implementation of the dictogloss technique not only improves the students' listening comprehension in the narrative text but also changes the students' behavior in teaching and learning process and motivated them. To sum up, the research finding proved that the implementation of the dictogloss technique improved the students' listening comprehension in the narrative text to the eleventh grade students of SMAN 5 Pontianak in the academic year 2017/2018. Keywords: dictogloss technique, listening comprehension, narrative text.